Efficacy of a concomitant elemental diet to reduce the loss of response to adalimumab in patients with intractable Crohn's disease. Issue 3 (22nd February 2018) - Sugita, Naoko; Watanabe, Kenji; Kamata, Noriko; Yukawa, Tomomi; Otani, Koji; Hosomi, Shuhei; Nagami, Yasuaki; Tanaka, Fumio; Taira, Koichi; Yamagami, Hirokazu; Tanigawa, Tetsuya; Shiba, Masatsugu; et al.
Abstract: Background and Aim: Secondary loss of response to adalimumab (ADA‐LOR) commonly occurs in patients with Crohn's disease (CD) treated with adalimumab (ADA). We evaluated the efficacy of concomitant elemental diet (ED) therapy to reduce ADA‐LOR in adult CD patients. Methods: Patients were divided into either an ED (≥900 kcal/day) or a non‐ED group (<900 kcal/day). Cumulative non‐ADA‐LOR rates were compared between groups. The effects of ED intake to reduce ADA‐LOR were also assessed in antitumor necrosis factor‐alpha (TNF‐α)‐naïve and infliximab (IFX)‐intolerant or refractory CD patients. Serum ADA and TNF‐α levels were measured. Results: We enrolled 117 CD patients into the ED ( n  = 25) or non‐ED ( n  = 92) groups. Although the cumulative non‐ADA‐LOR rate was higher in the ED group than in the non‐ED group, ED intake was not an independent reducing factor for ADA‐LOR (adjusted hazard ratio = 0.725; 95% confidence interval: 0.448–1.180; P  = 0.196) in all patients. ED intake was significantly more effective in reducing ADA‐LOR in IFX‐intolerant or refractory patients than in anti‐TNF‐α‐naïve patients in a dose‐related manner ( P for interaction <0.20). Serum ADA levels did not differ between the groups. Serum TNF‐α levels were significantly lower in the ED group than in the non‐ED group at week 28 ( P  = 0.044) and week 52 ( P  = 0.043). Conclusions: Concomitant ED therapy reduced ADA‐LOR in IFX‐intolerant or refractory patients in a dose‐related manner. Reductions in the TNF‐α levels by concomitant ED intake may contribute to reduce ADA‐LOR in CD patients.